Some new armascirine cunaxids (Acari: Prostigmata: Cunaxidae) from the Eastern United States - Skvarla, Michael; Dowling, Ashley P.g. (Zootaxa, 2012)
Four species of the family Cunaxidae (Acari: Acariformes), i.e. Armascirus ozarkensis sp. nov., A. pennsylvanicus sp. nov., A. primigenius sp. nov., and Dactyloscirus pseduophilippinensis sp. nov. are described and illustrated from the Ozark Highlands, Mississippi, and Appalachian Plateau. In addition, three described species, Armascirus gimplei, A. harrisoni, and Dactyloscirus dolichosetorus are reported from these areas. All new and previously described species have been registered with Zoobank. A list of species, including citations of their original description and Zoobank LSID numbers, and keys to world species of both genera have been included.